Laparoscopic Management of Ectopic Pregnancy Occurring Ten Years After Tubal Sterilization - Durukan, Tekin; Salman, Mehmet Coşkun; Atak, Zeliha; Özyüncü, Özgür; Velipaşaoğlu, Melih; Usubütün, Alp (Gynecology Obstetrics & Reproductive Medicine, 2009)
Ectopic pregnancy is still one of the leading causes of maternal mortality. Due to the popularity of elective sterilization procedures, the incidence of ectopic pregnancies following tubal sterilization began to increase in recent years and post-sterilization ectopic pregnancies account more than 10% of all ectopic pregnancies. This case report describes a 41-year-old woman with a diagnosis of an ectopic tubal pregnancy 10 years after laparoscopic tubal sterilization who was successfully managed via laparoscopy. Also, the incidence and risk factors for tubal sterilization failures, mechanisms of failure, and outcomes of failed cases are discussed.